The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s10886-009-9695-4
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Ant Cuticular Hydrocarbons

Abstract: We compared the published cuticular hydrocarbon (CHC) profiles of 78 ant species across 5 subfamilies. Almost 1,000 CHCs have been described for these species, composing 187 distinct homologous series and ten hydrocarbon groups. In descending order of occurrence were: n-alkanes > monomethylalkanes > dimethylalkanes > alkenes > dienes>> trimethylalkanes>> methylalkenes > methylalkadienes > trienes > tetramethylalkanes. Odd chain lengths and positions of methyl or double bonds at odd carbon numbers were far more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
207
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(225 citation statements)
references
References 91 publications
13
207
0
1
Order By: Relevance
“…Relative to other insects, there is a greater number of desaturase genes in ants 62 , although alkenes or polyunsaturated alkenes have not been found in all ants investigated 63 . Z. nevadensis nuttingi displays two alkadienes and two alkatrienes in the cuticular profile of reproductive individuals 49 , but the number of desaturases is at the lower end of the number of putatively functional desaturase genes found in ants (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 72%
“…Relative to other insects, there is a greater number of desaturase genes in ants 62 , although alkenes or polyunsaturated alkenes have not been found in all ants investigated 63 . Z. nevadensis nuttingi displays two alkadienes and two alkatrienes in the cuticular profile of reproductive individuals 49 , but the number of desaturases is at the lower end of the number of putatively functional desaturase genes found in ants (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 72%
“…Desaturase proteins are central to the production of alkenes, a highly variable component of cuticular hydrocarbons reported to transmit complex signals like nest-mate recognition cues in ants (Martin and Drijfhout 2009;van Zweden et al 2010). Manual annotation and phylogenetic analyses of the D9 and D11 desaturase gene families revealed that five ancestral subfamilies are present in all holometabolous insects (Supplemental Fig.…”
Section: Ant Genomes Harbor Thousands Of Taxonomically Restricted Genesmentioning
confidence: 99%
“…Although the CHCs of A. dobsoni have not been previously analyzed chemically, they consist of compounds that have been identified in several other insect taxa, reflecting a high degree of conservatism (Guédot et al 2009b; Martin et al 2008a; Martin and Drijfhout 2009 ). Sixty two percent of the CHCs we identified are also known on C. pyricola (Guédot et al 2009b ).…”
Section: Cuticular Hydrocarbon Profilementioning
confidence: 99%
“…The majority of the n alkanes and monomethyl alkanes likely provide protection against water loss. It is unlikely that n alkanes, and, to some extent, mono methyl alkanes, function as stable and distinctive communication signals (Gibbs and Pomonis 1995; Howard and Blomquist 2005; Martin and Drijfhout 2009 ) because these compounds are shared across taxa and vary considerably depending on environmental factors (Gibbs andPomonis 1995 ; Gibbs 1998 ).…”
Section: Cuticular Hydrocarbon Profilementioning
confidence: 99%